RECAMBIO TEMPORAL DE ESPECIES DE LEPIDÓPTEROS NOCTURNOS EN FUNCIÓN DE LA TEMPERATURA Y LA HUMEDAD EN UNA ZONA DE SELVA CADUCIFOLIA EN YUCATÁN, MÉXICO - Montero-Muñoz, Jorge L.; Pozo, Carmen; Cepeda-González, M. Fernanda (Instituto de Ecología, A.C., 2013)
The aim of this paper is to estimate the temporal of turnover pattern of moths species in relation to two environmental gradients: temperature (° C) and relative humidity(%). Using a light trap method, a community of moths were sampled for a period of 12 months, in the Kaxil Kiuic Biocultural Reserve located in Yucatán, Mexico. It was demonstrated that species turnover exhibits a strong temporal pattern in relation to temperature and relative humidity variation between climatic periods. The warm and dry period (March to July) had the highest dissimilatity in species composition, determined mainly by families: Noctuidae, Geometridae and Crambidae. This study provides information on the temporal pattern of temporal species turnover for families with high species richness of Neotropical moths. The results obtained have implications for conservation of moth biodiversity, since they allow a base line to be established, focused on detecting the effects of climatic variations on species composition.